1991
DOI: 10.1161/01.str.22.1.51
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated neuropathology by nilvadipine after middle cerebral artery occlusion in rats.

Abstract: We investigated the effects of nilvadipine, a calcium antagonist, on cerebral ischemia in rats. Under halothane anesthesia, 30 rats had a 3-0 nylon suture introduced through the ex'tracranial internal carotid artery to occlude the left middle cerebral artery. Nilvadipine was dissolved in polyethylene glycol 400. Immediately following occlusion, group 1 rats (n=10) were treated subcutaneously with vehicle and group 2 and 3 rats were treated with 1.0 (n=10) add 3.2 (n = 10) nig/kg nilvadipine, respectively. Pcrf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 28 publications
3
11
0
Order By: Relevance
“…These results are consistent with the data we reported previously (36). It was demonstrated that nilvadipine is effective against neuronal dysfunction in focal cerebral ischemia (37). Tanaka et al showed the effect of nilvadipine on the neuronal function of the cat brain after occlusion of the left middle cerebral artery (MCA) for 60 min followed by reperfusion for 90 min (38).…”
Section: Fig 7 Inhibition Of Cell Death By Administration Of Amlodisupporting
confidence: 92%
See 1 more Smart Citation
“…These results are consistent with the data we reported previously (36). It was demonstrated that nilvadipine is effective against neuronal dysfunction in focal cerebral ischemia (37). Tanaka et al showed the effect of nilvadipine on the neuronal function of the cat brain after occlusion of the left middle cerebral artery (MCA) for 60 min followed by reperfusion for 90 min (38).…”
Section: Fig 7 Inhibition Of Cell Death By Administration Of Amlodisupporting
confidence: 92%
“…Dipyridamole is a compound with multiple pharmacological actions, and it has also been reported to have an antioxidative effect (36,37). Our results showed that the effects of co-treatment with vitamin E or dipyridamole were not synergistic (Figs.…”
Section: Fig 7 Inhibition Of Cell Death By Administration Of Amlodimentioning
confidence: 49%
“…The inhibition of Ca2+ entry into cells may possibly serve as a measure for the treatment of cerebral ischaemia (Meyer et al, 1986;Germano et al, 1987;Kucharczyk et al, 1989;Kawamura et al, 1991 (Alps et al, 1988). On the other hand, nicardipine administered after bilateral carotid artery occlusion did not decrease the neurodegeneration .…”
Section: Discussionmentioning
confidence: 99%
“…44,45) The infarct brain tissue in the left MCA territory was differentiated using 2,3,5-triphenyltetrazolium chloride staining method. 46) Treated rats received 0.25 mg liposomeentrapped fasudil via the cisterna magna 2 h after ischemia insult and control rats received drug-free liposomes.…”
Section: Neuroprotective Effect In a Model Of Is-chemiamentioning
confidence: 99%